The pattern of hMENA isoforms is regulated by TGF-β1 in pancreatic cancer and may predict patient outcome. (1st December 2016) - Melchionna, Roberta; Iapicca, Pierluigi; Di Modugno, Francesca; Trono, Paola; Sperduti, Isabella; Fassan, Matteo; Cataldo, Ivana; Rusev, Borislav C.; Lawlor, Rita T.; Diodoro, Maria Grazia; Milella, Michele; Grazi, Gian Luca; et al.
ABSTRACT: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive disease in need of prognostic markers to address therapeutic choices. We have previously shown that alternative splicing of the actin regulator, hMENA, generates hMENA 11a, and hMENAΔv6 isoforms with opposite roles in cell invasion. We examined the expression pattern of hMENA isoforms by immunohistochemistry, using anti-pan hMENA and specific anti-hMENA 11a antibodies, in 285 PDACs, 15 PanINs, 10 pancreatitis, and normal pancreas. Pan hMENA immunostaining, absent in normal pancreas and low-grade PanINs, was weak in PanIN-3 and had higher levels in virtually all PDACs with 64% of cases showing strong staining. Conversely, the anti-invasive hMENA 11a isoform only showed strong staining in 26% of PDAC. The absence of hMENA 11a in a subset (34%) of pan-hMENA-positive tumors significantly correlated with poor outcome. The functional effects of hMENA isoforms were analyzed by loss and gain of function experiments in TGF-β1-treated PDAC cell lines. hMENA 11a knock-down in PDAC cell lines affected cell–cell adhesion but not invasion. TGF-β1 cooperated with β-catenin signaling to upregulate hMENA and hMENAΔv6 expression but not hMENA 11a In the absence of hMENA 11a, the hMENA/hMENAΔv6 up-regulation is crucial for SMAD2-mediated TGF-β1 signaling and TGF-β1-induced EMT. Since the hMENA isoform expression pattern correlates with patient outcome, the data suggest that hMENA splicing and related pathways are novel key players in pancreatic tumor microenvironment and may represent promising targets for the development of new prognostic and therapeutic tools in PDAC.